2023
DOI: 10.7717/peerj.16060
|View full text |Cite
|
Sign up to set email alerts
|

Fluorofenidone alleviates liver fibrosis by inhibiting hepatic stellate cell autophagy via the TGF-β1/Smad pathway: implications for liver cancer

Xiongqun Peng,
Huixiang Yang,
Lijian Tao
et al.

Abstract: Objectives Liver fibrosis is a key stage in the progression of various chronic liver diseases to cirrhosis and liver cancer, but at present, there is no effective treatment. This study investigated the therapeutic effect of the new antifibrotic drug fluorofenidone (AKF-PD) on liver fibrosis and its related mechanism, providing implications for liver cancer. Materials and Methods The effects of AKF-PD on hepatic stellate cell (HSC) autophagy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In the management of HCC, specific chemotherapeutic agents have demonstrated efficacy in halting tumor proliferation and metastasis by targeting the TGF-β/SMAD signaling cascade. Fluorofenidone (AKF-PD), an established drugs for idiopathic pulmonary fibrosis, also offers potential benefits for liver fibrosis by repressing HSC autophagy through the attenuation of the TGF-β1/SMAD pathway, potentially impeding the progression to HCC 128 . Sanguinarine (San), a natural benzo phenanthridine alkaloid, restrains tumor growth and HIF-1α signaling, and suppresses the expression changes of EMT markers as well as blocks p-SMAD2/3 translocation to the nucleus.…”
Section: The Role Of the Tgf-β/smad Pathway In The Prevention And Tre...mentioning
confidence: 99%
“…In the management of HCC, specific chemotherapeutic agents have demonstrated efficacy in halting tumor proliferation and metastasis by targeting the TGF-β/SMAD signaling cascade. Fluorofenidone (AKF-PD), an established drugs for idiopathic pulmonary fibrosis, also offers potential benefits for liver fibrosis by repressing HSC autophagy through the attenuation of the TGF-β1/SMAD pathway, potentially impeding the progression to HCC 128 . Sanguinarine (San), a natural benzo phenanthridine alkaloid, restrains tumor growth and HIF-1α signaling, and suppresses the expression changes of EMT markers as well as blocks p-SMAD2/3 translocation to the nucleus.…”
Section: The Role Of the Tgf-β/smad Pathway In The Prevention And Tre...mentioning
confidence: 99%
“…However, the clinical applicability and efficacy of these treatments require further validation through extensive clinical trials. Studies have shown that various chemotherapeutic agents, including Fluorofenidone (AKF-PD) ( 165 ), Sanguinarine (San) ( 166 ), Aspirin ( 167 ), Praziquantel (PZQ) ( 168 ), and Ursodeoxycholic acid (UDCA) ( 169 ), along with small molecule inhibitors such as Galunisertib (LY2157299) ( 170 172 ), LY2109761 ( 173 ), SKLB023 ( 174 ), and LY3200882 ( 175 ), are effective in treating HBV-HCC. The therapeutic vaccine Belagenpumatucel-L (Lucanix) ( 176 ) also exhibits efficacy in this setting.…”
Section: Tgf-βmentioning
confidence: 99%